Implementation of a Total Quality Management System for TDS Centers based on EFQM Excellence Model. WP5 Workshop - Castanheira, Isabel (2013)
Implementation of a Total Quality Management System based on EFQM Excellence Model, to question the performance and support the TDS Centers to overcome challenges to achieve sustainable excellence.